Efektivitas Pelatihan Perpajakan pada UMKM Fast Boat: Sebagai Upaya Peningkatan Kompetensi dan Kepatuhan Wajib Pajak - Lasmini, Ni Nengah; Jayanti Prita Utami, Made Ayu; Priyana, Putu Okta (E-Jurnal Akuntansi, 2023)
The low knowledge of tax administration in one of the fast boat MSMEs has an impact on several things, including MSME compliance in paying taxes, the accuracy of tax calculations, and the timeliness of tax reporting. This study aims to analyze the effectiveness of tax training as measured by the indicators of reaction, learning, behaviors, organizational results, and cost effectiveness. The method used in this research is descriptive method with a qualitative approach, this research is a field research, involving sixteen (16) informants. Data collection techniques used include observation, interviews, documentation with data analysis techniques, data reduction, data presentation, drawing conclusions and data verification. The results of this study, the training method used is a case study in the form of technical guidance in order to solve real problems related to PPh in fast boat SMEs. Tax training for fast boat SMEs has been effective so that it is expected to contribute to increasing taxpayer compliance which has implications for state revenue. Keywords: Effectiveness; Competency Improvement; MSME taxation; Tax Compliance